Coping Strategies in the Behavioral Models of Youth in Martial Law Conditions - Ihor Halian; Olena Halian; Mariia Myshchyshyn (Insight: the psychological dimensions of society, 2024)
The purpose of the study is to reveal the relationship between the manifestation of anxiety in youth and the coping strategies they use to overcome objectively and subjectively difficult life situations. Methods. The “Spielberger State-Trait Anxiety Inventory” (STAI) was used to determine the level of reactive and personal anxiety. Possible reactions to anxious and stressful situations were studied using the questionnaire “Coping Inventory for Stressful Situations” (CISS) (Parker & Endler, 1992). Statistical analysis methods included descriptive statistics methods, correlation analysis (Pearson), differentiation criteria (Student’s t-test, Fisher’s F-test, and eta-squared), and discriminant analysis with stepwise variable inclusion. The study sample consisted of 132 individuals aged 18–23. Results. The study diagnosed high levels of reactive (M = 53.42; SD = 12.103) and personal (M = 49.942; SD = 10.068) anxiety in the youth (overall sample). Differences in anxiety (t = 2.571; p < .05; d = .316) were statistically significant. Additionally, differences were found in the manifestation of personal (t = -3.902; p < .01; d = -1.140) and situational anxiety (t = -3.510; p < .01; d = -1.019) among men (M = 40.08; SD = 8.251) and women (M = 50.97; SD = 9.685). Young people (overall sample) use “avoidance” coping (M = 53.42; SD = 8.895) and problem-focused coping (M = 52.70; SD = 8.341). However, women (M = 48.13; SD = 10.911) compared to men (M = 39.69; SD = 8.149) are more likely to use emotion-focused coping (t = -2.644; p < .01; d = -.772). A direct correlation between personal anxiety and emotion-focused coping (R = .744; p < .01; R2 = .553) and an inverse correlation with problem-focused coping (R = -.276; p < .01; R2 = .076) were found. Situational anxiety is directly correlated with emotion-focused coping (R = .597; p < .01; R2 = .356). Discussion and Conclusions. The relationship between personal and situational anxiety in young people and defensive coping strategies (emotion-focused coping) was established. No statistically significant differences were found in problem-focused coping and avoidance-oriented coping. The results of the discriminant analysis showed the dominance of emotional coping, which accompanies both personal and situational anxiety. This negatively affects not only the success of activities but is also accompanied by physiological problems, reducing the quality of life and mental well-being of young people.